A prospective case-control study on the association of Rhinovirus nasopharyngeal viral load and viremia in South African children hospitalized with severe pneumonia - Baillie, Vicky L.; Moore, David P.; Mathunjwa, Azwifarwi; Morailane, Palesa; Simões, Eric A.F.; Madhi, Shabir A. (Journal of clinical virology, 2020)
•Rhinovirus role during severe childhood respiratory disease remains unknown.•Rhinovirus prevalence was similar between children with pneumonia and controls.•Rhinovirus-viremia was 4-fold more prevalent amongst cases than controls.•Viremia could be helpful in attributing causality to rhinovirus during pneumonia episodes. Rhinovirus (RV) role in pathogenesis of severe childhood disease remains controversial. We aimed to explore the association between RV molecular subtyping, nasopharyngeal viral loads and viremia with childhood pneumonia. Nasopharyngeal and blood samples from cases and controls were tested for RV and the 5′ non-coding region sequenced. The cases compared to controls had a similar prevalence of RV detection in the nasopharynx (23 % vs. 22 %, P = 0.66), similar RV species distribution (A, B, C = 44 %, 8%, 44 % vs. 48 %, 7%, 38 %; respectively; P = 0.66) and similar viral load (4.0 and 3.7 log10 copies/mL, P = 0.062). However, RV-viremia was 4.01-fold (aOR 95 % CI: 1.26–12.78) more prevalent among cases (7%) than controls (2%), P = 0.019. Furthermore, among cases and controls RV-C was more commonly associated with viremia (14 % and 4%, P = 0.023), than RV-A (2% and 1%; P = 0.529). Thus RV-viremia could be used as a measure for attributing causality to RV in children hospitalized for pneumonia.